The Agricultural Depression - Warren, G. F. (Quarterly Journal of Economics, 1924)
Wholesale prices not a measure of farm conditions, 184. — Index numbers of prices paid to farmers, 186. — Course of prices paid to farmers during the agricultural panic, 190. — Prices in different regions, 191. — Variation in effects on farmers of different ages, 192.— Purchasing power of farm products, 197. — Effect of a declining price level on agricultural prosperity, 198. — Other index numbers concerning the agricultural depression, 204.—Wages of farm and city labor, 207.—How declining prices are met in agriculture and industry, 209. — Relation of cheap food to the building boom, 211. — How long will agricultural depression continue? 213.